Aplikasi Reservasi Maintenance Kendaraan Berbasis SMS Gateway - Zulfan, Zulfan; Munawir, Munawir (KITA Institut, 2019)
Private or public vehicles as a means of transportation are now increasingly being used. This develops along with a large number of residents in their daily activities. With so many vehicles the need for vehicle maintenance centers is also growing. At present, the vehicle maintenance center is not proportional to the number of vehicles. This problem is seen by many vehicle users who are waiting to take care of their vehicles and some of them have to make reservations. Reservations made are still conventional in nature that is still making reservations at the vehicle maintenance center. Therefore, the purpose of this paper is to explain the making of the SMS Gateway vehicle reservation application. The method used is the Software Development Life Cycle (SDLC) using PHP, MySQL, and Gammu programming. This research produces an application that can make customers make vehicle maintenance reservations remotely using SMS media. And customers can receive information about vehicles that have been completed through maintenance via SMS sent via the application server.Keywords:Reservation, Vehicle, Information System, SMS gateway